2018
DOI: 10.3892/etm.2018.6327
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant rhubarb alleviates organs dysfunction and inhibits inflammation in heat stroke

Abstract: The aim of the present study was to investigate the effects of adjuvant rhubarb on the recovery of patients with heat stroke. A total of 85 patients with heat stroke were randomly assigned to two treatment groups: One group receiving conventional treatment for heat stroke (conventional group) and one group receiving rhubarb supplement in addition to conventional treatment (rhubarb group). Liver and kidney function parameters, Acute Physiology and Chronic Health Evaluation (APACHE) II scores, plasma interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…smoking and tiredness, may cause irreversible structural changes in a specific vascular territory 18 . However, the effect of cerebral ischemia on BBB, a diffusion barrier essential for maintenance of homeostasis and normal function of the central nervous system, has been broadly investigated 10 . In current study, we investigated the protection of the combination of TPG and TLPA on BBB by anti-inflammation, anti-oxidative stress and anti-apoptosis effects.…”
Section: Discussionmentioning
confidence: 99%
“…smoking and tiredness, may cause irreversible structural changes in a specific vascular territory 18 . However, the effect of cerebral ischemia on BBB, a diffusion barrier essential for maintenance of homeostasis and normal function of the central nervous system, has been broadly investigated 10 . In current study, we investigated the protection of the combination of TPG and TLPA on BBB by anti-inflammation, anti-oxidative stress and anti-apoptosis effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that 18 FDG was primarily aggregated in the kidneys, which is consistent with the increase observed in the creatinine levels of the mice. Earlier studies have investigated the pathogenesis of HS mainly in terms of systemic inflammation ( 54 ) or nervous system protection ( 55 ). The present study aimed to acquire a deeper understanding of the mechanisms underlying HS-induced AKI, which has been rarely studied and could provide novel insight.…”
Section: Discussionmentioning
confidence: 99%
“…AKI often manifests as oliguria, electrolyte imbalance, and elevated creatinine (Cr) levels, and requires continuous renal replacement therapy (6,7). The mechanism underlying the occurrence of AKI in EHS is not yet fully understood and may include hyperthermia, hypoperfusion, systemic inflammatory response syndrome (SIRS), disseminated intravascular coagulation (DIC), and rhabdomyolysis (8)(9)(10)(11)(12). Thus, a stable animal model is particularly important if the pathogenesis of EHS-AKI is to be studied in-depth.…”
Section: Introductionmentioning
confidence: 99%